Synergy: an old wisdom, a new paradigm for pharmacotherapy - Maique Weber Biavatti (Universidade de São Paulo, 2009)
Synergy is one of the governing principles of the natural world, and is one of the reasons for the increasing complexity of the evolutionary process. Broadly speaking, it relates to the cooperative effects produced by the interaction between various forces, elements, parts or individuals in a given context. Since the last century, some clinical studies have described the increased efficiency of a combination of drugs. To study the effects of the drug interactions, the most commonly cited model is that of Loewe, and the classical graphical representation is the iso-effect curve (isobologram). Plants contain an enormous diversity of specialized micromolecules, therefore there is a high likelihood of interactions between them. Through recent synergy studies, various synergistic interactions have been demonstrated among extracts of different plants, and between components of the same extract. Sinergia é um dos princípios que rege o mundo natural, apontado como uma das razões para a crescente complexidade do processo evolutivo. De uma forma ampla, ela se refere aos efeitos cooperativos produzidos pela interação entre diversas forças, elementos, partes ou indivíduos em um dado contexto. Desde o ultimo século, alguns estudos clínicos tem descrito a eficiência ampliada da combinação de fármacos. Para estudar os efeitos da interação de fármacos, o modelo mais citado é o da aditividade de Loewe, e também a representação clássica é o isobolograma, ou curva iso-efeito. As plantas contem uma diversidade enorme de micromoléculas especializadas, e consequentemente, alta probabilidade de interações entre elas. Através de estudos recentes dos efeitos sinérgicos, varias interações sinérgicas estão sendo demonstradas entre extratos de diferentes plantas e também entre componentes de um mesmo extrato.